A Sociolinguistic Analysis on the Types of English Course Instructor Code Switching in the English Teaching and Learning Process - Jamiluddin Jamiluddin (Institut Agama Islam Negeri Palopo, 2023)
This study focuses on sociolinguistics analysis towards the use of code switching produced by instructors in English teaching and learning (ELT) process. This study applied qualitative method and records the process of teaching English and interviews the instructors and students as a technique of this research to find the importance of code switching. The data were transcribed and analyzed use the concepts of Wardhaugh and Suwito about types of code switching and functions of code switching use the concept of Margana. The result shows that that there are 4 types of code switching used by instructors in English teaching and learning process. They are extern, intern, metaphorical and situational code switching.